Synthesis of Some New Bis-Heterocyclic Derivatives Based on 1,2,3-Triazoline and Study Their Antibacterial Activity - Jwad, Rasha Saad (Al-Nahrain Journal of Science, 2012)
Heptanol and octanol were converted into corresponding n-alkyl azides (2) using 48%HBr and sodium azide in two subsequent steps. Alkylation of diethyl malonate with allyl iodide and sodium ethoxide gave diethyl 2-allylmalonate (4) in a good yield. The reaction of compound (4) with urea in the presence of sodium ethoxide guide to obtain 5-allyl barbituric acid (5) in an excellent yield, while 4-allylpyrazolidine-3,5-dione (6) was obtained in very good yield by the reaction of compound (4) with hydrazine hydrate. The 1,3-dipolar cycloaddition reaction of compounds (5) and (6) with n-alkyl azides (2) afforded the targeted 1,2,3-triazolines (7a, 7b, 8a and 8b) in accepted yields. All the synthesized compounds had been characterized by TLC, FT-IR in addition to 1H NMR (7b and 8a). The antibacterial activity of the final compounds were evaluated against two types of bacteria Staphylococcus Aureus and Escherichia Coli, the results showed that most of the new triazolines possess high biological activity.